Effects of fibre orientation and layup on the mechanical properties of the pultruded glass fibre reinforced polymer tubes. (1st November 2019) - Al-saadi, Ali Umran; Aravinthan, Thiru; Lokuge, Weena
Highlights: The improvements of the tensile properties depend on fibre orientation and layup. The oriented fibre layers has an opposite actions on the compressive properties. The axial behaviour of columns is linear till the peak where capacity is dropped. Increase length of FRP tube changes the failure mode of square tubes nor circular. The compressive behaviour of FRP columns can be predicted well using FE analyses. Abstract: Pultruded glass fibre reinforced polymer (PFRP) tubes are becoming popular in civil engineering applications due to their unique features. The focus of this paper is on column applications. It addresses the understanding of the correlation between the mechanical properties of PFRP tubes and their material constituents. The burnout, tensile, compressive and shear tests were undertaken for square and circular PFRP tubes. Full scale compressive test was also conducted to compare the axial behaviour of pultruded FRP tubes. Moreover, a finite element analysis was carried out to simulate the compressive behaviour of full-scale specimens and to predict the axial behaviour of FRP columns of different length-to lateral dimension ratios. The results of compressive coupon tests are compared with those of full-scale tests which are used to check the accuracy of finite element simulation in terms of load-deflection curves, load capacity and failure mode. Results show that the strength and modulus depend on the fibre orientation and percentage of fibres in the axial direction. It further states the behaviour of full scale specimen is linear up to failure and the post peak behaviour of square tubes is affected by the continuity of non-axial fibre layers at corners. The numerical study reveals that the compressive behaviour of FRP tubes can be predicted reasonably.